Divergence in Implementation of Public Housing Saving Program: A Comparative Analysis of Indonesia, Singapore and Japan - Dynna D. Puspita; Andy Fefta W.; Romy Hermawan (Budapest International Research and Critics University, 2022)
After years of implementing a housing savings program called Taperum there is an inconclusive opinion that this program is deficient. This program, which was launched by the Central Government in 1993 and of which all civil servants were members, was compulsory. They paid a monthly fee that was automatically deducted from their salary. However, the fact showed that vast majority of them did not exploit this program. This study expects to empirically evaluate the factors behind the disappointment of this program to attract members for utilizing it until it was dissolved on March 24, 2018. Later, this program was repackaged into a new scheme under new management. Thus, this study additionally attempts to identify feasible recommendations for improving the viability of the new scheme. Such a program is unmistakably not the first to exist. There are even countries that have effectively managed it, like Singapore. Accordingly, to determine the possible approaches that Indonesia could adopt, comparative method is utilized. Moreover, this study analyzed the achievement factors of Singapore, and their chance of being embraced by Indonesia. Subsequently, it is hoped that this new scheme can be more utilized and valuable to its members.